Scheduling with Random Service Times - Rothkopf, Michael H. (Management Science, 1966)
This paper considers the problem scheduling of m immediately available tasks with random variable service times. It is shown that certain such problems can be reduced to equivalent deterministic problems. The existence of optimal schedules not involving the removal from service of incompletely processed tasks for some problems is proved and for other problems is disproved.